Stochastic Effects for the Reaction-Duffing Equation with Wick-Type Product. (16th October 2016) - Choi, Jin Hyuk; Lee, SeungGwan; Kim, Hyunsoo
Abstract : We construct new explicit solutions of the Wick-type stochastic reaction-Duffing equation arising from mathematical physics with the help of the white noise theory and the system technique. Based on these exact solutions, we also discuss the influences of stochastic effects for dynamical behaviors according to functionsh 1 ( t ), h 2 ( t ), and Brownian motionB ( t ) which are the solitary wave group velocities.